$ Manifestations of the poeticself in the poetry of Al-Sirri Al-Rafaa (Journal of the College of Basic Education, 2024)
This study seeks to examine (the manifestations of the self in the poetry of Al-Sirri Al-Rafaa), It is a study that emerges from the hypothesis that Al-Sirri’s poetry is a diverse creativity, Therefore, the research investigated the poet’s conditions and the manifestations of that self in his poetry by examining the most prominent manifestations of the self, His poetry, with the visions and experiences it carries, transports the recipient to other worlds that express the self’s position regarding living reality, We decided to study the self in his poetry, and when we extrapolated the self in his poetry, we found that it formed a unique pattern that represents the human will, It represents a network of interconnected and interconnected relationships between the individual himself and the society in which he lives, In this study, we have tried to identify aspects of the self in his poetry, It has become clear that the self is linked to the strong feelings and emotions that interrogate and express reality, This achieves the intended effect, Because it came from realistic experiences and creative artistic creation, The poet had situations, events, and facts that mimicked the human self that he expressed in his poetry, Which varied according to the diversity of the conditions of the self